Brain abscess due to Cladophialophora bantiana in an immunocompetent child: A case report - Ricky Master; Umesh Bhimani; Himanshu Tadvi; Ritesh Shah; Seema Balasubramaniam (Wolters Kluwer Medknow Publications, 2022)
Cladophialophora bantiana is a rare melanized neurotropic fungus. We report a case of cerebral pheohyphomycosis due to C. bantiana in an immunocompetent child. The patient was a 12-year-old male who presented with a headache, intermittent vomiting associated with decreased movements of the right upper and lower limbs, and right-sided deviation of the mouth. Brain magnetic resonance imaging showed multiple conglomerated lesions in the left gangliocapsular region and corona radiata with perilesional edema and mass effect and a few small ring-enhancing lesions also. Aspiration of brain abscess sent for a culture and isolated C. bantiana. The clinical and radiological presentations are similar to the common organisms such as tuberculosis and thus can be misleading while diagnosis. Despite aggressive management, the patient succumbed to his illness. It is imperative to isolate microorganisms, using all microbiological tests. Fungi should also be considered irrespective of the immunocompetency.